2015
DOI: 10.1017/s1368980015000543
|View full text |Cite
|
Sign up to set email alerts
|

Mid upper-arm circumference is an effective tool to identify infants and young children with severe acute malnutrition in India

Abstract: Objective: To assess the appropriateness of current mid upper-arm circumference (MUAC) cut-offs to identify children with severe acute malnutrition in India. Design: The analysis concerned 6307 children admitted to nutrition rehabilitation centres (2009)(2010)(2011) where they received therapeutic care as per guidelines by WHO and the Indian Academy of Pediatrics. Setting: States of Jharkhand, Madhya Pradesh and Uttar Pradesh, India. Subjects: Children aged 6-59 months with bilateral pitting oedema or weight-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…The 21 datasets’ characteristics are shown in Table 1 and the derived mortality data in Table 2 [ 16 , 36 , 39 – 41 , 44 58 ]. A brief description and comments on each study are given in Additional file 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The 21 datasets’ characteristics are shown in Table 1 and the derived mortality data in Table 2 [ 16 , 36 , 39 – 41 , 44 58 ]. A brief description and comments on each study are given in Additional file 2 .…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that arm muscles have better insulin sensitivity and higher insulin-mediated glucose clearance than leg muscles 28 . Thirdly, diminished nutrition or severe malnourishment, which is directly proportional to MAC, can be linked to an increase in the risk of mortality among infants and children 2931 . Therefore, it is important to detect malnutrition early, and MAC may be an efficacious and non-invasive tool to assess nutritional status and identify subjects with a high risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…38 Mid-upper arm circumference (MUAC) was measured for all participants to the nearest 0.1 cm at the midpoint of the left arm using a standardized tape ribbon. 39,40 Hookworm diagnosis and treatment. Children were asked to provide a fresh, morning fecal sample in a previously provided clean plastic cup.…”
Section: Methodsmentioning
confidence: 99%